Long-term results in malignant pleural mesothelioma treated with neoadjuvant chemotherapy, extrapleural pneumonectomy and intensity-modulated radiotherapy. Issue 1 (December 2015) - Thieke, Christian; Nicolay, Nils; Sterzing, Florian; Hoffmann, Hans; Roeder, Falk; Safi, Seyer; Debus, Juergen; Huber, Peter
Abstract Introduction We investigated the clinical outcome and the toxicity of trimodal therapy of malignant pleural mesothelioma (MPM) treated with neoadjuvant chemotherapy, extrapleural pneumonectomy (EPP) and adjuvant intensity-modulated radiotherapy (IMRT). Methods Chemotherapy regimens included Cisplatin/Pemetrexed, Carboplatin/Pemetrexed and Cisplatin/Gemcitabine, followed by EPP. 62 patients completed the adjuvant radiotherapy. IMRT was carried out in two techniques, either step&shoot or helical tomotherapy. Median target dose was 48 Gy to 54 Gy. Toxicity was scored with the Common Terminology Criteria (CTC) for Adverse Events. We used Kaplan-Meier method to estimate actuarial rate of locoregional control (LRC), distant control (DC) and overall survival (OS), measured from the date of surgery. Rates were compared using the logrank test. For multivariate analysis the Cox proportional hazard model was used. Results The median OS, LRC and DC times were 20.4, 31.4 and 21.4 months. The 1-, 2-, 3-year OS rates were 63, 42, 28 %, the LRC rates were 81, 60, 40 %, and the DC rates were 62, 48, 41 %. We observed no CTC grade 4 or grade 5 toxicity. Step&shoot and helical tomotherapy were equivalent both in dosimetric characteristics and clinical outcome. Biphasic tumor histology was associated with worse clinical outcome compared to epitheloid histology. Conclusions Mature clinical results of trimodal treatment for MPM were presented. They indicate that hemithoracic radiotherapy after EPP can be safely administered by either step&shoot IMRT and tomotherapy. However, the optimal prospective patient selection for this aggressive trimodal therapy approach remains unclear. This study can serve as a benchmark for current and future therapy concepts for MPM.